Tuesday

March 3, 2015

March 3, 2015

Posted by **Yoona** on Tuesday, January 3, 2012 at 12:04am.

- calculus -
**Steve**, Tuesday, January 3, 2012 at 12:30amy = ax^3 + bx^2 + cx + d

y' = 3ax^2 + 2bx + c

y'' = 6ax + 2b

y''(0) = 0

so b = 0

y'(2) = 0

so c = -12a

y(0) = 0

so d = 0

y = ax^3 - 12ax

y(2) = 4

so a = -1/4

y = -1/4 x^3 + 3x

y' = -3/4 x^2 + 3

y'' = -3/2 x

**Answer this Question**

**Related Questions**

Calculus - Let f(x) be a polynomial function such that f(-2)=5, f’(-2)=0 and f...

Calculus - Let f(x) be a polynomial function such that f(-2)=5, f'(-2)=0, and f...

Calculus - Let f(x) be a polynomial function such that f(4)=-1, f’(4)=2 and f”(4...

calculus - I needed help with these FRQ in my APCalc course. Any help or ...

Calculus - Which statement is NOT true of the graph f(x)=(x+1)(x-3)^2? A. f has ...

calculus - suppose f(x) is a function such that f(3)=5, f'(3)=0, and f''(3)=3. ...

calculus - Find the cubic function of the form y=ax^3 + bx^2 + cx + d which has ...

Pre-calculus - Find the critical point of the function y=-2(x-1)^2-3. Then, ...

Pre-calculus - Find the critical point of the function y=-2(x-1)^2-3. Then, ...

calculus - Find the relative max and relative min and the point of inflection, y...